LOS/LOSS/LOST. (1st May 2018) - Knight, Adam
LOS/LOSS/LOST explores how memory and architectural conservation are played out in Los Angeles. Structuring the text is a series of photographs taken by the artist of thirteen historical buildings designated 'lost' by the Los Angeles Conservancy. Writing embraces the motif of 'lostness' in biographical, artistic, literary and cinematic responses to the city. The essay attempts to parallel a longitudinal artistic project photographing former cultural monuments of the German Democratic Republic.